posted by .

(-6)-((-2)-5(2nd power)

5^2 = 25
-2 -25 = -27
-(-27) = 27
Subtract 6 from that.

-6-[-2-5(squared)]=
=-6-[-2-25]=
=-6-(-23)=
=-23+6
=-17

YOu have an error, Venessa, can you find it?

oops sorry i havn't done this in a while
thanx bobpursley

-6-(-2-5^2)=
=-6-(-2-25)=
=-6-(-27)=
(negatives cancel)
=-6+27=
=27-6=
=21

## Similar Questions

1. ### algebra 2

Find the constant term or the term independent of x in the expansion of (3x – 5/x to the 2nd power )and to the 9th power

please show me how to solve for 5m/m+1 divided by 25m to 2nd power divided by m to 2nd power + 6m +5
3. ### Math/Standard and scientific notation

Express each measure in standard form. (One more thing by the way you need this few prefixes) Tera= 10 to the 12th power Giga= 10 to the 9th power Mega= 10 to the 6th power Kilo= 10 to the 3rd power Pico= 10 to the -12th power Nano= …
4. ### Algebra

Factor each of following expressions x (4th power) - x (3rd power) - 6x (2nd power (a-b)(2nd power) - (a 2nd power + b) 2nd power
5. ### math

1. unite similar terms with parenthesis. x=2 y=-3 and z=5 find the value of ax to the 2nd power-cy+ax-2ax to the 2nd power+ 2cy to the 2nd power-ax-cy to the 2nd power+ ax to the 2nd power+ cy
6. ### elemmanarty algebra

Divide xy to 3rd power -3xy to 2nd power +2x to 2nd power y by xy